Gene Regulatory Network for Tapetum Development in Arabidopsis thaliana - Li, Dan-Dan; Xue, Jing-Shi; Zhu, Jun; Yang, Zhong-Nan (Frontiers in Plant Science, 2017)
In flowering plants, male gametophyte development occurs in the anther. Tapetum, the innermost of the four anther somatic layers, surrounds the developing reproductive cells to provide materials for pollen development. A genetic pathway of DYT1-TDF1-AMS-MS188 in regulating tapetum development has been proven. Here we used laser microdissection and pressure catapulting to capture and analyze the transcriptome data for the Arabidopsis tapetum at two stages. With a comprehensive analysis by the microarray data of dyt1, tdf1, ams and ms188 mutants, we identified possible downstream genes for each transcription factor. These transcription factors regulate many biological processes in addition to activating the expression of the other transcription factor. Briefly, DYT1 may also regulate early tapetum development via E3 ubiquitin ligases and many other transcription factors. TDF1 is likely involved in redox and cell degradation. AMS probably regulates lipid transfer proteins, which are involved in pollen wall formation, and other E3 ubiquitin ligases, functioning in degradating proteins produced in previous processes. MS188 is responsible for most cell wall-related genes, functioning both in tapetum cell wall degradation and pollen wall formation. These results propose a more complex gene regulatory network for tapetum development and function.